UNIVERSITY STUDENTS’ OBSTACLES IN SPEAKING ENGLISH - Irani Z, Ulfah; Rita Zahara; Riyan Maulana (CV Naskah Aceh, 2023)
This research aims at giving information about the students’ obstacles in speaking English. In this research, the writer applied a descriptive qualitative research. In this study, the writer used purposive sampling. The writer used questionnaire in collecting the data. In order to obtain the data for this study, the writer shared the questionnaires for students at STMIK Indonesia Banda Aceh, English for TOEFL preparation class with 15 students. The results of the study indicated that the students faced internal factors, unconfident and motivated during speaking English, the students faced topical knowledge difficulties in speaking performance, and the students’ external constraints affected them to speak English.